2023
DOI: 10.1049/htl2.12044
|View full text |Cite
|
Sign up to set email alerts
|

On the prediction of premature births in Hispanic labour patients using uterine contractions, heart beat signals and prediction machines

Abstract: Preterm birth is a global epidemic affecting millions of mothers across different ethnicities. The cause of the condition remains unknown but has recognised health‐based implications, in addition to financial and economic ones. Machine Learning methods have enabled researchers to combine datasets using uterine contraction signals with various forms of prediction machines to improve awareness of the likelihood of premature births. This work investigates the feasibility of enhancing these prediction methods usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This study is based on predicting premature births in Hispanic labour patients. The results have shown the use of two effective unsupervised learning methods, that is, GMM and K-means, towards the self-sorting of data samples based on the acquired physiological signals [55].…”
Section: Related Researchmentioning
confidence: 99%
“…This study is based on predicting premature births in Hispanic labour patients. The results have shown the use of two effective unsupervised learning methods, that is, GMM and K-means, towards the self-sorting of data samples based on the acquired physiological signals [55].…”
Section: Related Researchmentioning
confidence: 99%
“…Instead, prediction models using maternal features available from routine pregnancy care are more likely to be widely applicable and improve pregnancy outcomes. To improve predictive power of PTB, many popular ML algorithms have been employed and compared with traditional regression methods and achieved high areas under the receiver operating characteristic curve (AUC) (Fazzari et al, 2022;Park et al, 2022;Nsugbe et al, 2023). A number of studies found that logistic regression provided quicker and better classification performance, and easier interpretability than ML models in other disease settings (Kuhle et al, 2018;Song et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve an efficient prediction model, feature selection is an important process to reduce dimensionality and computing complexity, and facilitate clinical practice. There are two conventional ways to conduct feature selection: one is applying univariate analysis to select features which are highly associated with the outcome (Park et al, 2022;Nsugbe et al, 2023), another is relying on feature importance derived from ML algorithms (Sharifi-Heris et al, 2022;Espinosa et al, 2023). However, some known important features might be ignored when only relying on ML-based feature importance lists (Bose et al, 2019;Liverani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%